A Pilot Study of Lumped Parameter Model on Middle Cerebral Artery for Hemodynamic Parameters Assessment - Nurul Syazana Qhairunnessa Salleh; Ibrahim, Nabilah; Yousri, Nur’Afifah; Taib, Ishkrizat; Shanta, Shahnoor (Journal of Advanced Mechanical Engineering Applications, 2025)
The middle cerebral artery (MCA), especially the M1 and M2 segments, is critical in cerebrovascular health. Conventional imaging techniques for assessing atherosclerosis have limitations in accurately estimating boundary conditions for computational fluid dynamics (CFD) simulations. This initial study addresses these limitations by employing lumped parameter models (LPMs) to derive more precise boundary conditions for CFD simulations of blood flow in the MCA. The goal is to improve the accuracy of CFD models by integrating dynamic parameters such as resistance and compliance, which are essential for understanding localized hemodynamic changes due to atherosclerosis. Early stage highlighted the simulation of cerebral blood flow with LPMs, analyzing hemodynamic factors such as wall shear stress (WSS), pressure distribution, and flow rate, and visualizing these effects in the MCA. Using CFD and LPMs, this study offers the preparation of parameters setup for analyzing deeper mechanism of atherosclerosis alteration in cerebral circulation, potentially enhancing diagnostic accuracy and treatment strategies for stroke prevention.